1996
DOI: 10.1111/j.1365-2559.1996.tb01397.x
|View full text |Cite
|
Sign up to set email alerts
|

Medullary breast carcinoma vs. poorly differentiated ductal carcinoma: an immunohistochemical study with keratin 19 and oestrogen receptor staining

Abstract: Sixty breast carcinomas previously indexed as medullary carcinomas over a 24-year-period were reviewed and reclassified according to definitions suggested by Ridolfi et al. as typical medullary carcinoma, atypical medullary carcinoma, and non-medullary carcinoma. Paraffin sections of tumour tissue were examined by an avidin-biotin complex method using two keratin 19-specific monoclonal antibodies (BA17, DAKO and clone 170-2-14, Boehringer) and a monoclonal oestrogen receptor antibody (DAKO). For comparison 52 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2000
2000
2021
2021

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(4 citation statements)
references
References 12 publications
0
4
0
Order By: Relevance
“…ER and PgR expression has previously been reported in 37 of 106 [13][14][15] and seven of 16 cases of high grade conventional IDC, respectively. 13 In addition, HER2/neu overexpression was seen in 52 of 174 cases of high grade conventional IDC.…”
Section: Discussionmentioning
confidence: 99%
“…ER and PgR expression has previously been reported in 37 of 106 [13][14][15] and seven of 16 cases of high grade conventional IDC, respectively. 13 In addition, HER2/neu overexpression was seen in 52 of 174 cases of high grade conventional IDC.…”
Section: Discussionmentioning
confidence: 99%
“…Meanwhile, there has been attempts to find immunohistochemical markers that can differentiate medullary from nonmedullary carcinomas. Earlier reports about the lack of keratin 19 in medullary carcinoma 15 were later attributed to the type of antibody used, 16–17 with most currently used keratin 19 antibodies giving a positive result in the majority of cases. 16 In this issue of Histopathology , Tot confirms the presence of keratin 19 in most medullary and atypical medullary tumours.…”
Section: Cytokeratin Profilementioning
confidence: 99%
“…All typical medullary cases and most atypical cases seem to be oestrogen receptor (ER) negative. 17 On the other hand, a strikingly low incidence of progesterone receptors 17 and c‐ erbB ‐2 positive immunostaining 19–21 and a high incidence of p53 22–23 staining were reported in medullary carcinoma. But again, none of these findings is exclusive for medullary carcinoma and most of them are common in grade 3 invasive ductal tumours which constitute the main differential diagnosis.…”
Section: Cytokeratin Profilementioning
confidence: 99%
“…The concept that medullary carcinoma is a cytologically high-grade tumor has been confirmed by Ponsky et al, who found that medullary carcinomas show a strong tendency to be estrogen and progesterone receptor negative (23,24). Pedersen et al (25) and Cook et al (26) found that medullary carcinomas are more frequently aneuploid, with higher S-phase fractions than ductal carcinomas.…”
Section: Discussionmentioning
confidence: 93%